2011
DOI: 10.1111/j.1365-2745.2011.01826.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a mid-season period of low floral resources in a montane meadow ecosystem associated with climate change

Abstract: Summary1. Shifts in the spatial and temporal patterns of flowering could affect the resources available to pollinators, and such shifts might become more common as climate change progresses. 2. As mid-summer temperatures have warmed, we found that a montane meadow ecosystem in the southern Rocky Mountains of the United States exhibits a trend toward a bimodal distribution of flower abundance, characterized by a mid-season reduction in total flower number, instead of a broad, unimodal flowering peak lasting mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(152 citation statements)
references
References 36 publications
6
142
1
3
Order By: Relevance
“…Mesic meadows, the meadow types we expected to be most vulnerable, showed a particularly intriguing temporal trajectory, starting with higher abundance of hydric species and ending with a higher abundance of xeric affinity species. These results concur with Aldridge et al (2011), who found that the flowering-plant community in an alpine meadow shifted in floral resources during a drought and that the mesic meadows were most vulnerable to change. The implications of our data are that longer-term changes due to drought could simplify butterfly community composition, resulting in prevalence of a species tolerant to drying conditions and a loss of species associated with wetter conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Mesic meadows, the meadow types we expected to be most vulnerable, showed a particularly intriguing temporal trajectory, starting with higher abundance of hydric species and ending with a higher abundance of xeric affinity species. These results concur with Aldridge et al (2011), who found that the flowering-plant community in an alpine meadow shifted in floral resources during a drought and that the mesic meadows were most vulnerable to change. The implications of our data are that longer-term changes due to drought could simplify butterfly community composition, resulting in prevalence of a species tolerant to drying conditions and a loss of species associated with wetter conditions.…”
Section: Discussionsupporting
confidence: 81%
“…4), limiting divergence within the reproductive season. Thus, our results contrast with other studies in which experimental warming led to divergent flowering responses between species 9 and mid-season, low floral abundance as the climate warmed 16 . Longer active and reproductive periods by at least some species would reduce the adverse effects of warming on trophic interactions and ecosystem function 17,18 .…”
contrasting
confidence: 99%
“…Other studies have also found that elevated CO 2 has a greater effect on flowering times under warming conditions, as well as a greater effect on late-flowering species 14,20 . Our data indicate that higher atmospheric CO 2 concentrations may be contributing to observed changes over time in flowering patterns, such as a shorter reproductive season and greater asynchrony with pollinators, which have previously been attributed to warming 16,17 .…”
Section: Research Lettermentioning
confidence: 55%
“…Co-flowering patterns are important because they can affect the intensity of plant-plant interactions and rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120489 interactions with higher trophic levels, such as pollinators [51]. Indeed, we see evidence of community reshuffling of co-flowering patterns at Gothic [52,53] and changes in community-level flowering duration at Zackenberg [54].…”
Section: Discussionmentioning
confidence: 78%